Review of the Adoption of TQM Models and the Achieved Sustainable Business Results in the MENA Telecommunication Industry - Almusayebi, Afra; Hussein, Noor; Zeyoudi, Shaikhah; Obeidli, Maitha (European Journal of Business and Strategic Management, 2024)
Purpose: Understanding the criticality of the telecommunication industry in the current time and appreciating the significance of adopting total quality management models in organizations to extend business sustainability. This paper provides a comparison between two telecommunication leaders in the MENA region: Zain & Etisalat, to assess their adoption of TQM models and the impact on their organizational and market success. Methodology: this study uses a comparative case study. a mixed-methods methodology was applied, combining quantitative and qualitative data. Primary data collection methods included surveys given to employees at different levels to gauge the internal effects of TQM models on operational efficiency and employee satisfaction, as well as semi-structured interviews with key management personnel from both companies, aimed at gaining insights into the implementation and outcomes of TQM practices. Secondary data came from a number of sources, such as government publications that described TQM adoption and telecommunication trends, market analysis and financial performance data from industry databases like Statista, annual reports and official documentation from Zain and Etisalat, and relevant quality management certifications and standards (like ISO 9001:2015). Thematic analysis of interview transcripts to find recurring themes and implementation insights, content analysis of company reports and publications to evaluate the strategic alignment and integration of TQM models, and case study analysis to compare and contrast Zain and Etisalat's approaches to adopting and implementing TQM models were some of the qualitative data analysis techniques used. Findings: The study found that the adoption of TQM models like EFQM, Kaizen and Lean six sigma across the whole organization is more effective than localizing the application to one aspect as indicated by the comparison between Zain & Etisalat. The comparison indicated that the application of TQM extended the sustainability and resilience of Etisalat and Zain in the face of business challenges by improving performance and streamlining processes to increase customer satisfaction. Unique Contribution to Theory, Practice and Policy: The study recommended that both Etisalat and Zain should consider incorporating sustainability practices into their TQM frameworks, given the growing focus on corporate social responsibility and sustainability. This could be illustrating a dedication to sustainable business practices by coordinating Kaizen and Lean Six Sigma initiatives with objectives related to social responsibility and the environment. To improve the synergy between Kaizen, EFQM, and Lean Six Sigma initiatives, both companies should foster cross-functional collaboration.